PEG-conjugated pyrrole-based polymers: one-pot multicomponent synthesis and self-assembly into soft nanoparticles for drug delivery. Issue 66 (31st July 2019) - Moquin, Alexandre; Hanna, Ramez; Liang, Tongyue; Erguven, Huseyin; Gran, Evan Rizzel; Arndtsen, Bruce A.; Maysinger, Dusica; Kakkar, Ashok
Abstract : A simple one-pot methodology provides easy access to amphiphilic PEG–pyrrole backbone polymers, which self-assemble into soft nanoparticles enabling efficient drug loading/sustained release and can be detected inside cells. Abstract : Polyethylene glycol grafted pyrrole-based conjugated polymers are synthesized through a one-pot multicomponent methodology, the self-assemblies of which enable nanoparticle size-selective encapsulation of drug molecules and their sustained release. Efficient loading of curcumin through drug–nanoparticle core interactions is probed using FRET, and the inherently fluorescent nature of polypyrrole could be used to detect these nanocarriers intracellularly.